Pengembangan mata pencaharian alternatif bagi nelayan melalui kegiatan budidaya ikan dengan teknologi bioflok di Kampung Sungai Kayu Ara - Rusliadi Rusliadi; Iskandar Putra; Muhammad Fauzi; Niken Ayu Pamukas; Heri Masjudi (Riau Journal of Empowerment, 2018)
To increase the income of fishermen in Sungai Kayu Ara Village, Sungai Apit Sub-District, Siak Regency, alternative livelihoods are needed in the form of fish aquaculture using biofloc technology. For biofloc technology to be applied, the target community needs to be given knowledge and skills through counseling activities. Extension activities are carried out to improve the knowledge and skills of target communities so that they can apply fish cultivation with biofloc technology. The implementation of counseling uses the lecture method, discussion and demonstration of various materials presented. From the results of the activity, it was known that the target community seemed enthusiastic about the activities carried out, the participants began to understand and understand the material presented, and there was an increase in participants' knowledge about catfish farming with biofloc technology between 60-80%.